(untitled) (Marketing Journal, 2026)
Abstract This article examines global megatrends and their impact on Uzbekistanʼs economic policy. In particular, such areas as digital transformation, green economy, urbanization, and changes in the labor market are analyzed. The article analyzes the extent to which strategic documents and reforms adopted by the government of Uzbekistan are in line with global trends and considers opportunities for adaptation. The research results demonstrate the relevance of a megatrend-based approach in ensuring the long-term economic stability of the republic. Keywords: Megatrends, economic policy, digital transformation, green economy, urbanization, sustainable development, strategic planning.